The Idea of Pluralism in Indonesian Society: A Case Study of Cirebon City as a Cultural Melting Pot - Soekarba, Siti Rohmah (Journal of Strategic and Global Studies, 2018)
Indonesia is well-known as a country with diverse ethnicities, religions, and races. Although predominantly Muslim country, the largest population of Muslims of any country in the world today, the reminder of the population are Christians, Hindu, animist, or followers of varying Confucius and Buddhist beliefs. Indonesia today is not only a country with diverse religions, ethnicities, and races, but also a country with several challenges related to issues of religious pluralism.It takes the awareness and the political will to deconstruct what lies behind the various problems of the Indonesian nation by looking back to the Indonesian national identity as stated in the Pancasila principles and the 1945 Constitution. Indonesia's national motto, "Bhinneka Tunggal Ika" (Unity in Diversity), articulates the diversity that shapes the country. After the fall of Soeharto’s New Order regime, as a nation-state with a pluralistic society, Indonesia is prone to social unrest and intra-group tension in terms of race, ethnicity and religion. This paper focuses on two objects: first, the pluralism Indonesia’s social culture and the case study of Cirebon as a cultural melting pot. The interpretation and critical reflection on method used to explore that there had been constant contact with both India and China. Hinduism and Buddhism, and later Islam, came to Cirebon. The purpose of this research is to understand the pluralistic Indonesian society, particulalrly Cirebonese people and the practice respect for the people in everyday actions and words.